2021
DOI: 10.1126/science.abf1930
|View full text |Cite
|
Sign up to set email alerts
|

Response to Comment on “Circadian rhythms in the absence of the clock gene Bmal1

Abstract: Ness-Cohn et al. claim that our observations of transcriptional circadian rhythms in the absence of the core clock gene Bmal1 in mouse skin fibroblast cells are supported by inadequate evidence. They claim that they were unable to reproduce some of the original findings with their reanalysis. We disagree with their analyses and outlook.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…They could be the result of the mutation itself, a compensatory mechanism or false positives resulting from our analysis. The study by Ray et al, which report controversial findings regarding RNA rhythmicity in the Bmal1 -/mouse cells (NvCycle orthologous in Nematostella) is an interesting case of rhythmicity analysis to consider [34][35][36][37][38] . Our attempt to identify rhythmic genes faced challenges, particularly in the choice of statistical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…They could be the result of the mutation itself, a compensatory mechanism or false positives resulting from our analysis. The study by Ray et al, which report controversial findings regarding RNA rhythmicity in the Bmal1 -/mouse cells (NvCycle orthologous in Nematostella) is an interesting case of rhythmicity analysis to consider [34][35][36][37][38] . Our attempt to identify rhythmic genes faced challenges, particularly in the choice of statistical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a groundbreaking study demonstrated the maintenance of transcriptional rhythmicity despite the absence of a functional TTFL in Bmal1-deficient mouse cells [414]. However, this finding has sparked significant controversy among chronobiologists, leading to an intense debate regarding the validity of these results [415][416][417][418]. Whether eukaryotic redox and metabolic rhythms act solely as inputs and outputs or constitute the core of eukaryotic cellular timekeeping remains to be elucidated.…”
Section: Time Cues That Facilitate Rhythmic Cooperationmentioning
confidence: 99%